Botulinum toxin does not reverse the cortical dysfunction associated with writer's cramp. A PET study. - Ceballos-Baumann, A; Sheean, G; Passingham, R; Marsden, C; Brooks, D (1997)
Previous H2(15)O PET activation studies on patients with idiopathic torsion dystonia (ITD) have shown overactive striatum and frontal accessory areas and underactivity of the primary motor cortex and caudal supplementary motor area (SMA) during volitional movement. We have now examined activation of the motor system in healthy control subjects and patients with writer's cramp while they write a stereotyped word repetitively at a paced rate before and after treatment with botulinum toxin to see if these patients showed a similar pattern of abnormalities and whether they were reversible. As in ITD, our patients with writer's cramp showed impaired activation of the contralateral primary motor cortex, but enhanced activation of frontal association cortex. Botulinum-toxin treatment improved writing and increased activation in parietal cortex and caudal SMA. This may represent either a change in movement strategy or associated cortical reorganization secondary to deefferentation of alpha motor neurons. However, botulinum toxin failed to improve the impaired activation of the primary motor cortex. We conclude that, while botulinum toxin is clinically effective in writer's cramp, it does not reverse the associated dysfunction of primary motor and premotor cortex.